The Leaf Extract of Dysoxylum parasiticum (Osbeck) Kosterm. Contains Anti-oxidant and α-Glucosidase Inhibitor Activities: Leaf Extract of Dysoxylum parasiticum (Osbeck) Kosterm. - Wibawa, I Putu Agus Hendra; Hanafi , Muhammad; Butardo Jr , Vito M.; Mahon, Peter J. (Journal of Tropical Life Science, 2024)
The medicinal plant Dysoxylum parasiticum (Osbeck) Kosterm. (Meliaceae) is na- tive to Indonesia, but its bioactive potential has been little explored. This study de- termined the phenolic content, antioxidant, and antidiabetic activities of D. parasiti- cum leaf extracts. Dried, powdered leaves were sequentially extracted with hexane, ethyl acetate and methanol. Total phenolic and flavonoid contents were quantified by colorimetric assays. The ethyl acetate extract had the highest phenolic content at 21.54 mg gallic acid equivalents/g dry weight. Antioxidant capacity was evaluated by DPPH radical scavenging assay, while antidiabetic activity was assessed as inhi- bition of α-glucosidase enzyme. The ethyl acetate extract showed potent antioxidant (IC50 30.72 μg/mL) and α-glucosidase inhibitory (IC50 16.32 μg/mL) activities compared to standard controls. Putative bioactive components were identified by LC-MS/MS, including stylosin, capillartemisin A, 19β-glucosyl-14-deoxy-11,12- didehydroandrographoside, daturametelin H, stigmastan-3,6-dione, 2α,3β,4α-trihy- droxy nortropane and arnebinone. The traditional use of D. parasiticum is validated by its antioxidant and antidiabetic potential, which is associated with its phenolic content.